2020
DOI: 10.13083/reveng.v28i.974
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Estimation Methods of Reference Evapotranspiration in Bom Jesus ​​da Lapa, Ba

Abstract: Among the reference evapotranspiration (ETo) equations, the FAO-56 Penman-Monteith (PM FAO-56) model is considered the most accurate, but this model requires a greater amount of meteorological data. On the other hand, there are other methods that require fewer variables and have shown good precision according to the location. The objective of this work was to evaluate the efficiency of four methods for estimation of daily ETo, comparing them with FAO-56 PM equation in Bom Jesus da Lapa, Bahia, Brazil. To do so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Generally, the Hargreaves & Samani (736.4 mm) and Linacre (1262.6 mm) models were those ones that most underestimated ETo. The Benevides & Lopes (2309.5 mm) and Makkink (1947.8 mm) According to the parameterization of ETo when compared to the standard FAO56 method, studies show that methods such as Benevides & Lopes tend to overestimate the ETo values, making it an inefficient alternative for safe ETo estimates (COSTA et al, 2020). Nevertheless, studies showed that the Benevides & Lopes model can be an alternative to the FAO56 model when compared to other models that use T air .…”
Section: Eto Empirical Models Estimatesmentioning
confidence: 99%
“…Generally, the Hargreaves & Samani (736.4 mm) and Linacre (1262.6 mm) models were those ones that most underestimated ETo. The Benevides & Lopes (2309.5 mm) and Makkink (1947.8 mm) According to the parameterization of ETo when compared to the standard FAO56 method, studies show that methods such as Benevides & Lopes tend to overestimate the ETo values, making it an inefficient alternative for safe ETo estimates (COSTA et al, 2020). Nevertheless, studies showed that the Benevides & Lopes model can be an alternative to the FAO56 model when compared to other models that use T air .…”
Section: Eto Empirical Models Estimatesmentioning
confidence: 99%